143.4 W high power combined white supercontinuum source using a (7 × 1) supercontinuum fiber combiner - Sun, Chang; Ge, Tingwu; Cao, Kang; Wang, Zhiyong (Frontiers in Physics, 2022)
We demonstrate a 143.4 W high power combined white supercontinuum (SC) source using a (7 × 1) SC fiber combiner. Based on the criteria of adiabatic tapering and brightness conservation, a (7 × 1) SC fiber combiner is designed and theoretically investigated, and the simulated results of the transmission efficiencies of laser at different wavelengths of the combiner verify that the combiner has the ability of combining white SC sources efficiently. Then, the (7 × 1) SC fiber combiner is fabricated, and three white SC fiber laser sources with average power of about 50 W are set up for beam combining experiment. Finally, a 143.4 W high power combined white SC source is achieved with high combining efficiency of 97.4%. and the corresponding combined SC spectrum ranges from 450 nm to 1700 nm, which remains consistent with the overall spectral range of the three SC sources. The experiment result indicates that the (7 × 1) SC fiber combiner is greatly capable of combining high power white SC sources efficiently, thereby increasing the average power of the white SC source significantly. To the best of our knowledge, this is the first demonstration of a fiber combiner for high power white SC sources with such a high combining efficiency.